Pethia rutila (Teleostei: Cyprinidae), a new species from Mizoram, Northeast India - Lalramliana, Lalramliana; Knight, J. D. Marcus; Laltlanhlua, Zathang (Zootaxa, 2014)
Pethia rutila, a new species is described from Karnaphuli drainage, Mizoram, Northeast India. It is distinguished from its congeners in having a complete lateral line with 21–22 scales, an inconspicuous black humeral spot on the scale row below the 3rd and 4th lateral-line scales, a black blotch on the caudal peduncle centered above the insertion of the last anal-fin ray, overlapping lateral-line scales 16–18 or 17–19 and ½4/1/3½ scales in transverse line from dorsal-fin origin to pelvic-fin origin.